Reproductive potential and performance of fertility preservation strategies in BRCA-mutated breast cancer patients. (10th October 2017) - Lambertini, M; Goldrat, O; Ferreira, A R; Dechene, J; Azim Jr, H A; Desir, J; Delbaere, A; t'Kint de Roodenbeke, M -D; de Azambuja, E; Ignatiadis, M; Demeestere, I
Abstract: Background: Preclinical evidence suggests a possible negative impact of deleterious BRCA mutations on female fertility. However, limited and rather conflicting clinical data are available. This study assessed the reproductive potential and performance of fertility preservation strategies in BRCA -mutated breast cancer patients. Patients and methods: This was a retrospective analysis of two prospective studies investigating oocyte cryopreservation and ovarian tissue cryopreservation in newly diagnosed early breast cancer patients. In the current analysis, baseline anti-Mullerian hormone (AMH) and performance of cryopreservation strategies were compared between patients with or without germline deleterious BRCA mutations. Results: Out of 156 patients included, 101 had known BRCA status of whom 29 (18.6%) were BRCA -mutated and 72 (46.1%) had no mutation. Median age in the entire cohort was 31 years [interquartile range (IQR) 28–33). Median AMH levels were 1.8 μg/l (IQR 1.0–2.7) and 2.6 µg/l (IQR 1.5–4.1) in the BRCA -positive and BRCA -negative cohorts, respectively ( P  =   0.109). Among patients who underwent oocyte cryopreservation ( N  =   29), women in the BRCA -positive cohort tended to retrieve (6.5 versus 9; P  =   0.145) and to cryopreserve (3.5 versus 6; P  =   0.121) less oocytes than those in the BRCA -negative cohort. Poor response rate (i.e. retrieval of ≤4 oocytes) was 40.0% and 11.1% in the BRCA -positive and BRCA -negative cohorts, respectively ( P  =   0.147). Among patients who underwent ovarian tissue cryopreservation ( N  =   72), women in the BRCA -positive cohort tended to have a numerically lower number of oocytes per fragment (0.08 versus 0.14; P  =   0.193) and per square millimeter (0.33 versus 0.78; P  =   0.153) than those in the BRCA -negative cohort. Two BRCA- mutated patients were transplanted after chemotherapy and one delivered at term a healthy baby. No difference between BRCA1- and BRCA2- mutated patients was observed in any of the above-mentioned outcomes. Conclusion: A consistent trend for reduced reproductive potential and performance of cryopreservation strategies was observed in BRCA -mutated breast cancer patients. Independent validation of these results is needed.